Hb Presbyterian (HBB: c.327C>G) in a Nicaraguan Family. (2nd January 2017) - Pernudy-Ubau, Allan; Salinas-Molina, Jaslyn; Requenez, Yaneris; Ortiz-Lopez, Marianela; Puller, Ann-Christin; García-Rosales, Kenia; Rodríguez-Estrada, Anaishelle; Rodríguez-Romero, Walter; Mejía-Baltodano, Gerardo; Luo, Hong-Yuan; Chui, David H.K.
Abstract: Hemoglobin (Hb) is the protein responsible for oxygen transportation. It is a tetrameric protein comprising two α- and two β-globin subunits. In the literature, a large number of mutations in the α- and β-globin genes have been documented. Among these mutations, Hb Presbyterian ( HBB : c.327 C>G), is a naturally occurring mutant exerting low oxygen affinity. The C to G exchange (AA C >AA G ) at codon 108 of the β-globin gene results in the substitution of asparagine by lysine. Here, we document the identification of HBB : c.327 C>G in a 6-year-old female patient and her father from Nicaragua and Cuba, respectively. The presence of the abnormal Hb was confirmed by cellulose acetate electrophoresis, high performance liquid chromatography (HPLC) and genomic DNA sequencing. The β-globin gene sequences for both, father and daughter, disclosed the heterozygous mutation at codon 108 to be Hb Presbyterian or HBB : c.327 C>G. The mutant Hb was previously reported in four families from North America, Germany, Japan and Spain, respectively. This is the fifth family carrying HBB : c.327 C>G described to date and the first report from Latin America.